CHANGES IN LAND USE AS CONSEQUENCE OF DEMOGRAPHIC TRANSFORMATIONS OF RURAL TERRITORIES OF THE VOLGOGRAD REGION - N. V. Vishnyakov; D. A. Semenova (Юг России: экология, развитие)
Aim. Analysis of the population dynamics and changes in the share of arable land in the structure of land use separate territory for several historical periods, and to determine the causes of these changes. Methods. Studies have used forwarding, statistical methods, and the method of cartographic modeling and retrospective analysis. Results. Analysis of the results of the population census allows speaking about the general negative dynamics in the rural population of the Volgograd region in general and river basin Bolshaya Golubaya in particular. Historical and cartographic analysis has shown the dependence of the arable lands of the number of residents on the territory residents. In addition, the population of the territory is significantly affected by soil fertility. Main conclusions. The population of the river basin Bolshaya Golubaya over the past hundred years have steadily decreased, as due to various socio-economic reasons, such as consolidation of rural settlements, the planned destruction of farm system, moving people into the city, and due to the difficult climatic conditions for farming: poor soil fertility, high degree of erosion areas, poor soil conditions of the territory.